Fishing for Human Perceptions in Coastal and Island Marine Resource Use Systems - Hans von Storch (Frontiers Research Topics, 2018)
Human perceptions, decision-making and (pro-) environmental behaviour are closely connected. This Research Topic focuses on bringing together perceptions and behaviour for sustainable coastal and island marine resource use systems. Management and governance of (large and small-scale) coastal marine resource use systems function in highly complex social and ecological environments, which are culturally embedded, economically interest-led and politically biased. Management processes therefore have to integrate multiple perspectives as well as perception-driven standpoints on the individual as well as the decision-makers' levels. Consequently, the analysis of perceptions has developed not only as part of philosophy and psychology but also of environmental science, anthropology and human geography. It encompasses intuitions, values, attitudes, thoughts, mind-sets, place attachments and sense of place. All of these influence human behavior and action, and are collected or are available within the respective marine resource use system, which may support the livelihood of a large part of the local population. Management and governance are not only about mediating between resource use conflicts or establishing marine protected areas, they deal with people and their ideas and perceptions. Understanding the related decision-making processes on multiple scales and levels hence means much more than economically assessing the available marine resources or existing threats to the associated system. Over the past decade, there has been a growing inter- and transdisciplinary international community becoming interested in research which integrates perceptions of coastal and inland residents, local and regional stakeholder groups, as well as resource and environmental managers and decision-makers. By acknowledging the importance of the individual perspective and interest-led personal views, it became obvious how valuable and important these sources of information are for coastal research. An increase of research effort spent on the link between perceptions and behaviour in marine resource use systems is thus both timely and needed. By offering a diversity of inspiring and comprehensive contributions on the link between perceptions and behaviour, this Research Topic aspires to critically enlighten the discourse and applicability of such research for finding sustainable, locally identified, anchored and integrated marine resource use pathways.